The Effect of Education Through Video on Retaining Knowledge of Pregnant Women About Nutrition to Prevent Stunting - Alfrensya Clara Patty; Yulian Wiji Utami; Fransiska Imavike Fevriasanty (Universitas Aisyah Pringsewu, 2023)
During pregnancy, a mother will experience various physical and mental changes that will affect her life. In pregnancy, nutrition is vital because by getting optimal nutrition, pregnant women will stay healthy and prevent babies from experiencing Stunting. This study aims to see the effect of education through video media on the knowledge retention of pregnant women to prevent Stunting. This study used a quasi-experimental design with a pretest-posttest design with a control group design, where respondents were divided into two groups, the treatment group: using video media and the control group: using booklet media. Data analysis using sample test paired t-test. A total of 60 respondents participated in this study. The results showed a significant effect on knowledge retention of pregnant women before education, after education, two weeks after education and one month after. The research results obtained a significant level of 0.000 (r value less than a), which means that education through video media and booklet media affected the retention of pregnant women's knowledge about nutrition to prevent Stunting. Family knowledge determines the nutritional status of pregnant women and prospective babies. Health workers need to develop health education for families to prevent Stunting. Abstrak: Pada masa kehamilan, seorang ibu akan mengalami berbagai macam perubahan baik dari segi fisik maupun segi mental yang akan mempengaruhi kehidupannya. Dalam proses kehamilan gizi memiliki peranan yang sangat penting sebab dengan mendapatkan gizi yang optimal ibu hamil akan tetap sehat dan dapat mencegah bayi mengalami stunting. Penelitian ini bertujuan untuk melihat pengaruh edukasi melalui media video terhadap retensi pengetahuan ibu hamil untuk mencegah stunting. Penelitian ini menggunakan desain quasi experiment dengan rancangan pretest-posttest with control group design, dimana responden dibagi menjadi 2 kelompok, kelompok perlakuan: dengan menggunakan media video dan kelompok kontrol: dengan menggunakan media booklet. Analisa data menggunakan uji sampel paired t-test. Sejumlah 60 responden yang turut berpartisipasi dalam penelitian ini. Hasil penelitian menunjukkan bahwa terdapat pengaruh signifikan retensi pengetahuan ibu hamil sebelum pemberian edukasi, setelah pemberian edukasi, 2 minggu setelah edukasi dan 1 bulan setelah pemberian edukasi dengan nilagi signifikansi sebesar 0.000 kurang dari 0.05 atau (r value kurang dari a), artinya ada pengaruh pemberian edukasi melalui media video dan media booklet terhadap retensi pengetahuan ibu hamil tentang gizi untuk mencegah stunting. Pengetahuan keluarga menentukan status gizi ibu hamil dan calon bayi. Penting bagi tenaga kesehatan untuk mengembangkan pendidikan kesehatan bagi keluarga untuk mencegah stunting.